COMPREHENSIVE REVIEW ON THE ENHANCING CRITICAL ELEMENTS OF ICARE IN THE ER NURSE’S WORK SETTING - 1Abdullah Eidhah Abdullah Alorayf, 2Abdulaziz Ahmad Saleh Al Saleh, 3Ali Mohammed Abdullah, 4Abdullah Hussein Saleh Al Lajam, 5Mohammed Ahmad Alasseri, 6Badr Mahdi Mana Al yami, 7All Hussaln Mana Alyami, 8Salem Zaid Ali Alsuliman (Chelonian Research Foundation, 2022)
This orderly audit analyzes the basic components of iCare (intelligent communication) within the Emergency Room (ER) doctor office setting. iCare is an advancing concept that combines innovative propels and compassionate, patient care. This audit draws on existing writing to distinguish key components, challenges, and openings for joining iCare in the ED. This article proposes techniques to progress iCare utilization, support patient of care, and move forward results and nnurse fulfillment through a framework investigation. Suggestions are advertised to direct future research about and practices to progress iCare within the crisis department. Keywords: iCare, Emergency Room, Nurse, patient care, Comprehensive Assessment, Integrated Care, Holistic Approach